Depression Demographic Profiling of Young Adults in South Africa - Bambo, Matsidiso Princess (University of the Witwatersrand, Johannesburg, 2024)
In young people aged 15 and 29 years, mental illnesses accounted for 23% of Years Lived with Disability (YLD) and among mental disorders, depressive disorders emerged as the second largest worldwide contributor to YLD at approximately 5.6%. In addition, one in every six individuals suffered from depression in South Africa. However, there is limited recent research about the demographic characteristics of South African emerging adults who may be vulnerable to depression. This research aimed to conduct demographic profiling of emerging adults (N=819) in South Africa who present with depressive symptoms. Additionally, using Pearson’s Product-Moment Correlation, T-test, and ANOVA, this cross- sectional research analysed secondary data from the Africa Long Life Study to determine relationships as well as statistical differences among demographic variables and depressive symptoms. Results indicated a low presence of depression in the sample. Significant relationships were found between depressive symptoms and demographic variables (socioeconomic status and religiosity). While no significant differences were found among language groups, a higher presence of depressive symptoms was found among females and those experiencing moderate to great financial difficulties. The findings emphasised the critical need for mental health policies and initiatives that promote prevention or early detection, prevention, and enhanced access to quality mental healthcare, particularly among vulnerable emerging adults like females and individuals who are economically disadvantaged. Mental health interventions should adopt comprehensive approaches that incorporate aspects of religiosity and spirituality to buffer against the presence of depressive symptoms among emerging adults
A research report Submitted in fulfillment of the requirements for a Master of Arts in Social and Psychological Research in the Department of Psychology, In the Faculty of Humanities , School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; emerging adults; demographics; depressive symptoms; South Africa; SDG-3: Good health and well-being